High Thermoelectric Performance in the Wide Band‐Gap AgGa1‐xTe2 Compounds: Directional Negative Thermal Expansion and Intrinsically Low Thermal Conductivity. (20th December 2018) - Su, Xianli; Zhao, Na; Hao, Shiqiang; Stoumpos, Constantinos C.; Liu, Mengyuan; Chen, Haijie; Xie, Hongyao; Zhang, Qingjie; Wolverton, Chris; Tang, Xinfeng; Kanatzidis, Mercouri G.
Abstract: A deficiency of Ga in wide band‐gap AgGa1‐ x Te2 semiconductors (1.2 eV) can be used to optimize the electrical transport properties and reduce the thermal conductivity to achieve ZT > 1 at 873 K. First‐principles density functional theory calculations and a Boson peak observed in the low temperature heat capacity data indicate the presence of strong coupling between optical phonons with low frequency and heat carrying acoustical phonons, resulting in a depressed maximum of Debye frequency in the first Brillouin zone and low phonon velocities. Moreover, the AgTe bond lengths and TeAgTe bond angles increase with rising temperature, leading to a significant distortion of the [AgTe4 ] 7− tetrahedra, but an almost unmodified [GaTe4 ] 5− tetrahedra. This behavior results in lattice expansion in the ab ‐plane and contraction along the c ‐axis, corresponding to the positive and negative Gruneisen parameters in the phonon spectral calculations. This effect gives rise to the large anharmonic behavior of the lattice. These factors together with the low frequency vibrations of Ag and Te atoms in the structure lead to an ultralow thermal conductivity of 0.18 W m −1 K −1 at 873 K. Abstract : A significant distortion of the [AgTe4 ] 7− tetrahedra but an almost unchanged [GaTe4 ] 5− tetrahedra in the structure of AgGaTe2 upon heating leads to lattice expansion in the ab‐plane and contraction along the c ‐axis, producing a large anharmonicity in the lattice and intrinsic low thermal conductivity. Maximum ZT above 1 is achieved through Ga deficiency in wide band‐gap AgGa1‐ x Te2 semiconductors.